MODEL PEMBELAJARAN PBL UNTUK MENGANALISIS STRUKTUR DAN KEBAHASAAN TEKS LAPORAN HASIL OBSERVASI DENGAN MENGGUNAKAN TEKNIK NUMBER HEAD TOGETHER - WINNY SENIATI W (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2023)
The low reading motivation of grade 10 students refers to the poor learning outcomes of students. In addition, media and learning models that are not precise cause a lack of students' ability to analyze the structure and language of the text of the observation report. Therefore, teachers are required to carry out creative and innovative learning. The author applies a scientific approach with the Problem Based Learning learning model in learning to analyze the structure and language of editorial texts for 10th grade students at SMKN 7 Bandung. The learning process is carried out by applying the Numbered Head Together technique. Learning activities are designed according to the syntax of Problem Based Learning, focusing on the activeness of students, and problem oriented. This Problem Based Learning learning model improves students' reading skills and improves the ability to analyze the structure and language of the text of the observation report. This can be seen from the level of participation of students in asking and responding to group presentations that appear. By applying the Problem Based Learning learning model, students are given the opportunity to define sentences with definitions and descriptions of various objects. The results of these best practices can be concluded that the Problem Based Learning learning model can increase students' reading interest and can improve student learning outcomes in the learning process analyzing the structure and language of the text of the observation report. ABSTRAKRendahnya motivasi membaca peserta didik kelas 10, merujuk pada hasil belajar peserta didik yang kurang juga. Selain itu media dan model pembelajaran yang kurang tepat menyebabkan kurangnya kemampuan peserta didik dalam menganalisis struktur dan kebahasaan teks laporan hasil observasi. Oleh karena itu, guru dituntut untuk melakukan pembelajaran yang kreatif dan inovatif. Penulis menerapkan pedekatan saintifik dengan model pembelajaran Problem Based Learning pada pembelajaran menganalisis struktur dan kebahaasaan teks editorial pada peserta didik kelas 10 di SMKN 7 Bandung. Proses pembelajaran yang dilakukan adalah dengan menerapkan teknik Numbered Head Together. Aktivitas pembelajaran dirancang sesuai dengan sintak Problem Based Learning, berfokus pada keaktifan peserta didik, dan berorientasi pada masalah. Model pembelajaran Problem Based Learning ini meningkatkan kemampuan membaca peserta didik dan meningkatkan kemampuan menganalisis struktur dan kebahasaan teks laporan hasil observasi. Hal ini dapat dilihat dari tingkat partisipasi peserta didik dalam bertanya dan menanggapi presentasi kelompok yang tampil. Dengan menerakan model pembelajaran Problem Based Learning peserta didik diberi kesempatan untuk menentukan kalimat definisi dan deskripsi dari berbagai objek. Hasil best practies ini dapat disimpulkan bawa model pembelajaran Problem Based Learning ini dapat meningkatkan minat baca peserta didik dan dapat meningkatkan hasil belajar peserta didik dalam proses pembelajaran menganalisis struktur dan kebahasaan teks laporan hasil observasi.